An investigation of the gender differences in creative thinking abilities among 8th and 11th grade students. (September 2015) - Bart, William M.; Hokanson, Brad; Sahin, Iclal; Abdelsamea, Mohammed Abdelhady
Highlights: Females and males in 8th and 11th grades display differences in creative thinking. Females in 8th grades perform higher than males on subtests of TTCT except fluency. Males and females in 11th grades perform equivalently on fluency and originality subtests. Females in 11th grades register higher creativity scores than males on three TTCT subtests. Gender differences in creative thinking have educational implications. Abstract: This study investigated the gender differences in creative thinking subtests between males and females among 8th and 11th grade students. A suburban independent public school district in Minnesota provided student responses to the Torrance Creative Thinking Test (TTCT) Figural Form A. The sample included 996 8th and 748 11th grades students. One-way ANOVAs were used to analyze the differences between males and females in the two study samples. Results of the study revealed that there were statistically significant differences on the majority of the subtests between males and females in favor of the females among both the 8th and 11th grade students. However, there were no statistically significant differences in the fluency subtest between males and females among the 8th grade students. The results also revealed that there were no statistically significant differences in the fluency and originality subtests between males and females among the 11th grade students. Educational implications and suggestions for future work were presented.